Managing Strategy-Culture Dichotomies in South African Municipalities: A Payment Culture Perspective - Enwereji, Prince; Uwizeyimana, D. E. (International Review of Management and Marketing, 2021)
Local municipalities in South Africa have been struggling to enhance a payment culture for municipal services. Despite their endeavours to do so, consumer debts still intensify to an unbearable extent. This study investigated how to manage strategy-culture dichotomies to enhance a payment culture for municipal services. Secondary data were gathered from several sources, such as journal articles, books, blogs, magazines, and local municipal reports. A systematic literature review was done to examine the effective measures needed to manage the strategy-culture dichotomies in effect to change and handle peoples’ culture and psychology in the payment for municipal services. The meaning of culture and its impact on the implementation of the organisational strategy were identified. Concerning the intensifying consumer debt accruals, the study upholds that strategic leaders should understand the cultural imperatives of the people before making and implementing strategies. The study further recommends that municipal employees identify characteristics of present culture and specify actions to implement a strategy. More so, strategic leaders should always scrutinise their workforce, analyse their systems, improve their communication options, and collaborate with stakeholders. This study asserts that the intensifying consumer debts amidst varying cultural imperatives could be stemmed by reconciling strategy-culture dichotomies. Keywords: Local municipality; Organisational strategy; Culture; Payment culture; Service provision. JEL Classification: H70 DOI: https://doi.org/10.32479/irmm.11662